Information technology for management : current research and future directions : 17th Conference, AITM 2019, and 14th Conference, ISM 2019, Held as Part of FedCSIS, Leipzig, Germany, September 1-4, 2019, Extended and Revised Selected Papers /: current research and future directions : 17th Conference, AITM 2019, and 14th Conference, ISM 2019, Held as Part of FedCSIS, Leipzig, Germany, September 1-4, 2019, Extended and Revised Selected Papers. (2020) - Unknown
No abstract available